PENGEMBANGAN MEDIA MOVIE MAKER PADA MATA PELAJARAN KEARSIPAN KELAS X ADMINISTRASI PERKANTORAN - Fika Dwi Rahmania; Sutrisno -; I Nyoman Suputra (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2016)
Abstract: The purpose of this research is the instructional medium movie maker in the basic competence that is Identifying the Archival Equipment and Materials also Explaining the Entry and Exit Mail for students in grade X of Office Administration program membership SMK PGRI 6 Malang. This study used a model of development ASSURE combined, and it is modified with 4D developmental model thus obtained 7 stages of development. Based on the validation results of the experts of media and material, the experts of media showed the percentage of 100% and the experts of material showed the percentage of 96.87%that those numbers showed that the instructional medium movie maker has very valid criteria. The results of the validation by a small group of students showed a percentage of 82% was obtained from the results of the empirical score divided by the maximum score. The results of the validation by a large group of students showed a percentage of 81.7% was obtained from the results of the empirical score divided by the maximum score.Abstrak: Tujuan penelitian ini untuk menghasilkan produk media pembelajaran movie maker dalam kompetensi dasar Mengidentifikasi Alat dan Bahan Kearsipan serta Menjelaskan Pengurusan Surat Masuk dan Keluar untuk siswa kelas X program keahlian Administrasi Perkantoran SMK PGRI 6 Malang. Penelitian ini menggunakan model pengembangan ASSURE yang digabungkan dan dimodifikasi dengan model pengembangan 4D sehingga di peroleh 7 tahap pengembangan. Berdasarkan hasil validasi ahli media dan ahli materi, dimana ahli media menunjukkan bahwa persentase sebesar 100% dan ahli materi menunjukkan bahwa persentase sebesar 96,87% dimana jumlah tersebut menunjukkan bahwa media pembelajaran movie maker memiliki kriteria sangat valid. Hasil validasi oleh siswa kelompok kecil menunjukkan persentase sebesar 82% di peroleh dari hasil skor empirik dibagi skor maksimal. Hasil validasi oleh siswa kelompok besar menunjukkan persentase sebesar 81,7% di peroleh dari hasil skor empirik dibagi skor maksimal.